2018
DOI: 10.2174/1874364101812010264
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Error among Male Primary School Students in Jazan, Saudi Arabia: Prevalence and Associated Factors

Abstract: Background:Refractive error is a common and serious eye disorder that affects more than 153 million people globally. The aim of this study was to estimate the prevalence and pattern of refractive error among male primary school children in Jazan region, Saudi Arabia.Methods:A cross-sectional study was conducted among a randomly selected group of 395 students (aged 6-14 years) in Jazan region, Southwest Saudi Arabia. An optometrist and medical students assessed the refraction error using an autorefractor, a Sne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
6
12
1
3
Order By: Relevance
“…The study participants who had 2–4 and >4 hours per day mobile exposure were 3.69, 11.6 times more to develop myopia as compared to those who had < 2 hours per day exposure respectively. This finding is consistent with studies done in India [ 14 , 25 ], Saudi Arabia [ 28 ], and Debere Markose, Ethiopia [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study participants who had 2–4 and >4 hours per day mobile exposure were 3.69, 11.6 times more to develop myopia as compared to those who had < 2 hours per day exposure respectively. This finding is consistent with studies done in India [ 14 , 25 ], Saudi Arabia [ 28 ], and Debere Markose, Ethiopia [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies from the above define myopia without spherical equivalent and also they used a cut-off point of > -1.00 Diopter whereas the present studies used a cut-off point of > -0.50 Diopter. On the contrary, the result of this study is slightly lower as compared to studies done in Gondar, Ethiopia (11.9%) [2] and much lower than the studies conducted in America (41.5%) PLOS ONE [7], Israeli (28.3%) [24], Taiwan (21%) [4], Beijing China (80.7%) [3], Hong Kong China (36.7%) [8], Delhi India (13.1%) [25], North India (21%) [14], Qingdao (22.6%) [26], Amman Jordan (17.6%) [27], and Saudi Arabia (17.2%) [28]. This difference might be because of the variation in race between the study participants and of Asian descent.…”
Section: Plos Onementioning
confidence: 99%
“…Proportion of severely reduced VA however gets higher. This may attribute to ocular development during children's hyperopic reserve stage, and this situation is consistent with other studies that revealed the predominant uncorrected refractive errors in children aged 6-7 years being hyperopia and astigmatism [18,19].…”
Section: Resultssupporting
confidence: 91%
“…Proportion of severely reduced VA however gets higher. This may attribute to ocular development during children’s hyperopic reserve stage, and this situation is consistent with other studies that revealed the predominant uncorrected refractive errors in children aged 6–7 years being hyperopia and astigmatism [ 18 , 19 ]. However this was not furtherly examined in this study.…”
Section: Discussionsupporting
confidence: 91%